The Role of Brand Trust in Mediating Social Media Marketing Effects on Orlenalycious Brand Loyalty - Made Dwika Cahya Putri; I Gusti Ayu Ketut Giantari (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This study aims to analyze the role of brand trust in mediating the influence of social media marketing on brand loyalty in Orlenalycious, an MSME brand known for its brownie products. In an increasingly competitive industry, building strong relationships with customers has become essential, and social media marketing is becoming one of the effective ways to achieve this. This research was conducted in Denpasar City using questionnaires distributed to 120 respondents online and offline. The sampling technique used is non-probability sampling with the purposive sampling method. The results of the study showed that all the hypotheses put forward were accepted. Social media marketing has been proven to have a positive and significant effect on brand loyalty, as well as on brand trust. In addition, brand trust also has a positive and significant influence on brand loyalty. Interestingly, brand trust can mediate the influence of social media marketing on brand loyalty in part. These findings support the Stimulus-Organism-Response (S-O-R) model, which emphasizes the importance of social media marketing in influencing consumer attitudes and behaviors through accurate information and in accordance with the promises of the products offered. The implications of this study show that in order to increase brand loyalty, Orlenalycious needs to continue to provide up-to-date information and fulfill product promises through social media marketing, so as to strengthen consumer trust and increase brand loyalty. These results are expected to be a guide for MSME managers in designing more effective marketing strategies, especially in utilizing social media to build long-term relationships with customers.